Prevalencia de resistencia de Helicobacter pylori a la Amoxicilina: revisión de literatura y aproximación al enfoque metodológico (2020)
Helicobacter pylori is considered a bacterium capable of generating some important health pathologies such as: chronic gastritis, ulcers and gastric adenocarcinoma. Currently, the treatments used for the eradication of this microorganism are based on a combination of a gastric acid suppressor with the use of antibiotics such as clarithromycin, levofloxacin, metronidazole and amoxicillin. However, the high percentage of resistance to the antibiotics used to eradicate this bacterium has made it difficult to treat the infections it causes, especially in those cases in which the presence of multi-resistant strains is evident. One of the fundamental antibiotics for therapy is amoxicillin, however, currently there are few studies in the country on the prevalence of H. pylori resistance to this antibiotic. With the purpose of knowing the current situation of the resistance of this agent to amoxicillin both globally, regionally and in Colombia, this work had as objectives i) to review the literature on the subject and ii) to carry out a first practical approach using a molecular approach. The review includes articles from different geographical areas in order to determine the factors that promote the development of resistance in bacteria. The experimental work used well conserved H. pylori DNA as a starting point, followed by an in vitro amplification of specific fragments of the pbp1A gene of this bacterium a conventional PCR. It was proposed to carry out the sequencing of the amplified fragments and a bioinformatic analysis to determine possible point mutations that will generate changes in the gene sectioned as a target. Based on the above, the literature review will obtain a clear overview of the developed topic, with emphasis on some of the mutations that can confer resistance to amoxicillin to Helicobacter pylori.